An MRI‐compatible patient rotation system — design, construction, and first organ deformation results. Issue 2 (16th February 2017) - Whelan, Brendan; Liney, Gary P.; Dowling, Jason A.; Rai, Robba; Holloway, Lois; McGarvie, Leigh; Feain, Ilana; Barton, Michael; Berry, Megan; Wilkins, Rob; Keall, Paul
Abstract : Purpose: Conventionally in radiotherapy, a very heavy beam forming apparatus (gantry) is rotated around a patient. From a mechanical perspective, a more elegant approach is to rotate the patient within a stationary beam. Key obstacles to this approach are patient tolerance and anatomical deformation. Very little information on either aspect is available in the literature. The purpose of this work was therefore to design and test an MRI‐compatible patient rotation system such that the feasibility of a patient rotation workflow could be tested. Methods: A patient rotation system (PRS) was designed to fit inside the bore of a 3T MRI scanner (Skyra, Siemens) such that 3D images could be acquired at different rotation angles. Once constructed, a pelvic imaging study was carried out on a healthy volunteer. T2‐weighted MRI images were taken every 45° between 0° and 360°, (with 0° equivalent to supine). The prostate, bladder, and rectum were segmented using atlas‐based auto contouring. The images from each angle were registered back to the 0° image in three steps: (a) Rigid registration was based on MRI visible markers on the couch. (b) Rigid registration based on the prostate contour (equivalent to a rigid shift to the prostate). (c) Nonrigid registration. The Dice similarity coefficient (DSC) and mean average surface distance (MASD) were calculated for each organ at each step. Results: The PRS met all design constraints and was successfully integrated with the MRI scanner. Phantom images showed minimal difference in signal or noise with or without the PRS in the MRI scanner. For the MRI images, the DSC (mean ± standard deviation) over all angles in the prostate, rectum, and bladder was 0.60 ± 0.11, 0.56 ± 0.15, and 0.76 ± 0.06 after rigid couch registration, 0.88 ± 0.03, 0.81 ± 0.08, and 0.86 ± 0.03 after rigid prostate guided registration, and 0.85 ± 0.03, 0.88 ± 0.02, 0.87 ± 0.02 after nonrigid registration. Conclusions: An MRI‐compatible patient rotation system has been designed, constructed, and tested. A pelvic study was carried out on a healthy volunteer. Rigid registration based on the prostate contour yielded DSC overlap statistics in the prostate superior to interobserver contouring variability reported in the literature.